1998
DOI: 10.1057/ori.1998.2
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the prison population

Abstract: This paper describes the development of a new methodology tor making long ' term projections of the Prison Population. The mn ethodologv is based on a flow model of offenders in and oui of prison, allowing the effect of changes in court sentencing policy to be predicted. The heart of the methodology is a new theory of offending, al/owing the number of first time offenders to be predicted and also the recidivism ot those released from prison.-00000-In 1996 the Operational Research Unit of the Home Office was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Both approaches have been previously used for modelling the prison population system. DES models of the prison population have been developed by Kwak et al (1984), Cox et al (1978), Korporaal et al (2000), and SD models have been developed in Bard (1978), andMcKelvie et al (2007), while the UK prison population model by Grove et al (1998) is a flow model analogous to an SD model.…”
Section: The Case Studymentioning
confidence: 99%
“…Both approaches have been previously used for modelling the prison population system. DES models of the prison population have been developed by Kwak et al (1984), Cox et al (1978), Korporaal et al (2000), and SD models have been developed in Bard (1978), andMcKelvie et al (2007), while the UK prison population model by Grove et al (1998) is a flow model analogous to an SD model.…”
Section: The Case Studymentioning
confidence: 99%
“…Several factors can have an impact on LOS, such as a country's jurisdiction, changes in criminal justice policy (Grove, MacLeod, & Godfrey, 1998), changes in the organization of a country's mental health system (Sharma et al, 2015), and patient characteristics (Davoren et al, 2015;Dumont et al, 2012;Moran, Fragala, Wise, & Novak, 1999;Shah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The modelling exercise used as the stimulus for inducing modellers' thoughts asked expert modellers to build models of the UK prison population, based on a study reported by Grove et al (1998). The UK prison population problem was considered suitable because it is sufficiently self-contained to enable the development of a simulation model in a limited time period of around 60 minutes.…”
Section: The Modelling Exercisementioning
confidence: 99%